Self-Organized Wrinkling in Thin Polymer Films under Solvent-Nonsolvent Solutions: Patterning Strategy for Microfluidic Applications - Singh N.; Verma A.; Sachan P.; Sharma A.; Kulkarni M.M. (My University, 2025)
Self-organized wrinkling instabilities in thin polymer films have instigated a field of versatile surface patterning and have spurred several research efforts in developing micro- and nanopatterned templates for a wide range of applications. Here, we report for the first time a distinct class of wrinkles in a thin polymer (polystyrene, PS) film coated on a substrate under a mixture of organic solvent and aqueous nonsolvent. The solvent (dimethyl formamide, DMF) softens and swells the polymer and paves the way for wetting of the hydrophilic substrate (≥46 mJ/m2) by the solvent-nonsolvent (S-NS) mixture, leading to wrinkle formation. It is investigated that selective delamination-induced wrinkling is a generic phenomenon and takes place in various polymers as well as different combinations of solvent-nonsolvent mixtures. The surface energy of the substrate and the composition of the solvent-nonsolvent mixture play a critical role as wrinkling is not observed on substrates with lower surface energy (<46 mJ/m2). An isotropically distributed yet disordered self-organized wrinkle network of hollow buried channels is formed, and it is illustrated that these can be exploited to generate a mesh of microwires and harnessed to form highly directional patterns using electron beam lithography, which can turn the new leaf for nano- and microfluidic device fabrication platforms. ©